-1
$\begingroup$

Consider the system:

$$ y(s)=b\frac{e^{−sτ}}{s+a}u(s) $$

where a,b are unknown, constant parameters and $\ τ>0 $ is an unknown delay constant. How can I obtain a plant parametric model for this system in the following form ?

$$ z = \theta^{*T}\phi \ + η $$

which satisfies the following condition:

  • $\tau = 0 \Rightarrow η = 0 $
$\endgroup$
  • $\begingroup$ So $\theta$ should contain $a$, $b$ and $\tau$? $\endgroup$ – fibonatic Feb 11 at 4:16
  • $\begingroup$ $θ$ should contain $a,b$ and $η$ should contain $τ$. If $τ=0$ then $η$ should be also 0. $\endgroup$ – Teo Protoulis Feb 11 at 8:55
  • $\begingroup$ Do you want to linearize the nonlinear model? If so, why don't use a Taylor series? $\endgroup$ – Ken Grimes Feb 11 at 17:07
  • $\begingroup$ I want to obtain a linear parametric model of the form stated at the question where $θ^{*T} = [a \ b]$. $\endgroup$ – Teo Protoulis Feb 11 at 17:10
2
$\begingroup$

Solution to the linear parameterization of the given system:

$\ y = \frac{b}{s+a}e^{-sτ}u = \frac{b}{s+a}e^{-sτ}u \ + \ \frac{b}{s+a}u \ - \ \frac{b}{s+a}u = \frac{b}{s+a}u \ + \ \frac{b}{s+a}(e^{-s\tau} \ - \ 1)u $

$$ sy = -ay+bu+b(e^{-s\tau}-1)u $$

We filter both sides of the equation with a stable first order filter

$$ Λ(s) = s + l_1, \ l_1 >0 $$

and the final parametric model is now:

$\ \frac{s}{Λ(s)}y = -a\frac{1}{Λ(s)}y+b\frac{1}{Λ(s)}u+ \frac{b}{Λ(s)}(e^{-s\tau}-1)u$

And the last equation can be written in the form:

$$ z = \theta^{*T}\phi + η $$

where $\ z = \frac{s}{Λ(s)}y, \ \theta^* = [a \ b], \ \phi = [-\frac{1}{Λ(s)}y \ \ \frac{1}{Λ(s)}u]^T $ and $\ η = \frac{b}{Λ(s)}(e^{-sτ}-1)u $.

It is obvious that for $\ \tau = 0 \to η=0. $

The new input vector of the parametric system $\ z $, can be derived directly from the input of the initial system $\ y. $

EDIT: Slightly different approach

$$ \frac{s}{Λ(s)}y = -a\frac{1}{Λ(s)}y+b\frac{1}{Λ(s)}u+ \frac{b}{Λ(s)}(e^{-s\tau}-1)u $$

From this point, we can come up with a linear parametric model which contains the initial input vector $\ y $ following the procedure below:

$$ Λ(s) = s + l_1 \Rightarrow s = Λ(s) - l_1, \ l_1>0$$

$$ \frac{Λ(s) - l_1}{Λ(s)}y = -a\frac{1}{Λ(s)}y+b\frac{1}{Λ(s)}u+ \frac{b}{Λ(s)}(e^{-s\tau}-1)u \Rightarrow $$

$$ \frac{Λ(s)}{Λ(s)}y - \frac{l_1}{Λ(s)}y = -a\frac{1}{Λ(s)}y+b\frac{1}{Λ(s)}u+ \frac{b}{Λ(s)}(e^{-s\tau}-1)u \Rightarrow $$

$$ y = -(a-l_1)\frac{1}{Λ(s)}y +b\frac{1}{Λ(s)}u+ \frac{b}{Λ(s)}(e^{-s\tau}-1)u $$

and the last equation can be written in the form:

$$ y = \theta^{*T}\phi + η $$

where $\ \theta^* = [(a-l_1) \ \ b], \ \phi = [-\frac{1}{Λ(s)}y \ \ \frac{1}{Λ(s)}u]^T $ and $\ η = \frac{b}{Λ(s)}(e^{-sτ}-1)u $.

It is obvious that for $\ \tau = 0 \Rightarrow η=0. $

| improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ It is worth nothing that $s\,y$ is not causal (not poper). Therefore, one can also apply a low pass filter to both sides of the equation and since $\theta^*$ is constant this is equivalent to applying the low pass filter to your $z$ and $\phi$. $\endgroup$ – fibonatic Feb 15 at 23:12
  • $\begingroup$ Forgot the filter, I edited the answer. $\endgroup$ – Teo Protoulis Feb 15 at 23:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.